Resposta :
Resposta:
Explicação passo-a-passo:
[tex]a) \left(11\right)\cdot \:2+\left(11\right)\cdot \:2 \:\:\:(multiplicar\:e\:dividir\:da\:esquerda\:para\:a\:direita) (11) x 2:22\\22+22=44[/tex]
[tex]b) \left(-9\right)x+\left(-9\right)y\mathrm{Fatorar\:o\:termo\:comum\:}-9=-9\left(x+y\right)[/tex]
[tex]c) \left(\left(-5\right)\cdot \:2\right)\cdot \:4\mathrm{Remover\:os\:parênteses}:\quad \left(a\right)=a=-5\cdot \:2\cdot \:4\mathrm{Multiplicar\:os\:numeros:}\:5\cdot \:2\cdot \:4=40\\=-40[/tex]
[tex]d) \left(\left(7\right)\cdot \:5\right)\cdot \:2\mathrm{Remover\:os\:parênteses}:\quad \left(a\right)=a=7\cdot \:5\cdot \:2\mathrm{Multiplicar\:os\:números:}\:7\cdot \:5\cdot \:2=70[/tex]
[tex]e) \left(\left(-4\right)\cdot \:2\right)x\mathrm{Remover\:os\:parênteses}:\quad \left(a\right)=a=-4\cdot \:2x\mathrm{Multiplicar\:os\:números:}\:4\cdot \:2=8\\=-8x[/tex]